Collective Behavior and Social Movements in the Late-August 2025 Demonstrations: Solidarity and Mass Violence in the Case of Affan Kurniawan - Erizal Erizal; Ninda Zahra Wahyudi; Regita Alma Danita; Marie Muhammad Wildan; Dwiandra Firdaus (LPPM Institut Pendidikan Nusantara Global, 2026)
This study investigates the dynamics of collective behavior and social movements that emerged during the late-August 2025 demonstrations in Indonesia, focusing on how structural grievances, triggering events, and media framing shaped the escalation of public mobilization. The research aims to explain why the protests, which initially centered on opposition to proposed parliamentary allowance increases, quickly expanded into a nationwide movement marked by strong expressions of solidarity and episodes of mass violence. Special attention is given to the death of Affan Kurniawan, an ordinary citizen who became an unintended victim during crowd-control operations, and whose case transformed the public’s emotional and moral engagement with the demonstrations. Using a qualitative approach that combines interviews with civil society actors, analysis of organizational documents, and observations of mainstream and digital media content, the study identifies several key findings. Structural economic and political tensions created fertile conditions for mobilization, while the death of Affan Kurniawan acted as a powerful moral catalyst that broadened participation across diverse social groups. Civil society organizations played a crucial role in coordinating information, framing human-rights concerns, and maintaining the momentum of public engagement. Meanwhile, contrasting media narratives contributed to divergent interpretations of the protests, influencing public sentiment and state responses. The study concludes that interactions among grievances, symbolic events, and communication networks significantly amplify the scale and emotional intensity of contemporary social movements. Strengthening transparency, accountability, and rights-based approaches in protest management is essential to prevent similar escalations in the future.